1958
DOI: 10.1113/jphysiol.1958.sp005999
|View full text |Cite
|
Sign up to set email alerts
|

The carbon monoxide dissociation curve of human blood

Abstract: The complete dissociation curve of carboxyhaemoglobin has not been studied since Douglas et al. (1912), using the more accurate and convenient methods available at the present time. COHb dissociation curves have therefore been determined in the absence of oxygen, at three different C02 pressures, for the blood of three normal subjects. These curves have been compared with the corresponding 02Hb curves. METHODSFor each experiment 20-25 ml. of venous blood was freshly drawn into a syringe, the dead space of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

1965
1965
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 13 publications
3
23
1
Order By: Relevance
“…Further precise data of Joels & Pugh (1958) and Roughton (1965) confirmed that the equilibrium curve for 02 cannot be obtained from that for CO by using a simple scale factor, M. The same conclusion was also reached on the basis of kinetic studies (Gibson, 1959). The value of M is sensitive to temperature and varies with pH (Roughton, 1954;Joels & Pugh, 1958). The results of Allen & Root (1957) suggest that M reaches a maximum value in whole blood at a plasma pH of 7-4.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Further precise data of Joels & Pugh (1958) and Roughton (1965) confirmed that the equilibrium curve for 02 cannot be obtained from that for CO by using a simple scale factor, M. The same conclusion was also reached on the basis of kinetic studies (Gibson, 1959). The value of M is sensitive to temperature and varies with pH (Roughton, 1954;Joels & Pugh, 1958). The results of Allen & Root (1957) suggest that M reaches a maximum value in whole blood at a plasma pH of 7-4.…”
Section: Introductionsupporting
confidence: 59%
“…The estimation of the four individual equilibrium constants for CO, by Roughton (1954), and for 02 by Roughton, Otis & Lyster (1955), supported this argument. Further precise data of Joels & Pugh (1958) and Roughton (1965) confirmed that the equilibrium curve for 02 cannot be obtained from that for CO by using a simple scale factor, M. The same conclusion was also reached on the basis of kinetic studies (Gibson, 1959). The value of M is sensitive to temperature and varies with pH (Roughton, 1954;Joels & Pugh, 1958).…”
Section: Introductionsupporting
confidence: 55%
“…P0oand pressure. The data of Rodney et al (1969) would suggest that neither pH nor pressure has any effect on M. They discount earlier data of Roughton (1954), Allen & Root (1957) and Joels & Pugh (1958) …”
Section: Jhcontrasting
confidence: 53%
“…Godin and Shephard (1972) calculated the diffusion coefficient of CO to Mb to be 0.1 ml CO s À1 mmHg À1 . Assuming an increase in HbCO content by 5%, the increase in pCO in blood is 0.02 mmHg [Joels and Pugh 1958; i.e. that within 300 s (mean time of minutes 4 and 6) after starting the CO-rebreathing of 60 ml CO, 0.6 ml CO is bound to Mb].…”
Section: Co-diffusion To Extravascular Compartmentsmentioning
confidence: 99%